Organization of Training Process for Preparation to 10x10 Shuttle Run Exam - Malkov A. A. (Interactive science, 2020)
analysis of literature sources showed insufficient coverage of the issue of preparation for passing the standards in the exercise Shuttle run 10*10 m. You can find a General description of the exercise, but without specific recommendations, or General recommendations for preparing for the 60 – 100m test. Although the method of preparation for the 60, 100 m competition is similar to the method of preparation for the 10*10 m shuttle run, it still has a number of fundamental differences. This article contains tools, methods, and practical recommendations for preparing for implementation. standard shuttle run 10*10 m.
Keywords: нормативы; быстрота; standards; челночный бег 10*10 м; физическое тестирование; челнок; 10*10 м; контрольная проверка; shuttle run 10*10 m; physical testing; swiftness; shuttle; 10*10 m; test check